Ex Ante Moral Hazard in the Health Insurance Market in Indonesia - Hindarti, Sri (Jurnal Indonesia Sosial Sains, 2022)
This paper will empirically examine the existence of ex ante moral hazard in health insurance market in Indonesia with respect to lifestyle choices such as smoking and obesity. A key challenge in understanding the moral hazard problem is endogeneity. Decisions regarding having insurance and lifestyle choices are arguably sequential, not simultaneous. Then, it is difficult to decide which one precedes the other. To address this problem, this paper uses a multivariate probit analysis. This paper uses three waves from the IFLS (Indonesian Family Life Survey) over 2000, 2007, and 2014, as these have information about insurance status, smoking behavior, and obesity condition. This paper finds evidence of the existence of ex ante moral hazard in health insurance for obesity of the head of household, but not for smoking. The multivariate probit regression shows that having health insurance increases the propensity of being obese. Using a wider sample, including all members of households, there is not sufficient evidence of the existence of ex ante moral hazard for either smoking or obesity. Surprisingly, the decisions between smoking and obesity are substitutes. This means that there are non-observable elements that increase the tendency to smoke, but reduce the propensity of being obese, and vice versa.